Biogas Production from Cow Manure Using an Anaerobic Digestion Technique - Al Umairi, Abdul Rahim; Al Amri, Hatem; Al Kalbani, Abdullah; Al Hadidi, Al Hussain; Al Hashami, Marwan (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
The world is suffering from limited sources of energy thus finding a renewable and sustainable source is very crucial. Cow manure is an unexploited treasure and is expected to have a high potential for energy recovery. This study aimed to evaluate biogas production from cow manure (CM) under an anaerobic condition. The cow manure was collected from a local farm in Oman and diluted with a ratio of 1:3 (dry CM/Water). The diluted cow manure (DCM) was characterized and found to have pH 7.9, total solids (TS) 8930 mg/L, total dissolved solids (TDS)1390 mg/L, dissolved organic carbon (DOC) 8160 mg/L and electrical conductivity (EC) 2730 µS/cm. The used anaerobic reactor (20 litres, black) was fed with DCM (15 litres) and operated at atmospheric mesophilic conditions (40 to 45 C). The gas was measured by the water displacement method. The results revealed that the biogas was generated in low amounts after three days (119 mL) and achieved more than 20 litres after nine days. The percentage of volatile solids to total solids was found to be 71% and the production of the biogas was calculated as 131 L/kg VS. This study is believed to pave the way for reducing the pressure on landfills and converting an environmental burden into a product of added value serving the circular economy theme.